1996
DOI: 10.1002/etc.5620150523
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial interference in whole‐effluent toxicity tests

Abstract: Abstract-Routine National Pollutant Discharge Elimination System (NPDES) cooling-water toxicity tests demonstrated an acute effect on Ceriodaphnia dubia and fathead minnows (Pimephales promelas). Test results were characterized by irregular mortality dose-response curves and a brown filamentous mass on the opercular area of affected fish. Some fish and Ceriodaphnia also became entrapped in filamentous material present on the bottom of the test vessels. Microscopic examination of test fish revealed severe fouli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 1 publication
(1 reference statement)
0
6
0
Order By: Relevance
“…Large variation in survival of fathead minnow larvae among replicates has been observed by others (T. Norberg-King, U.S. Environment Protection Agency [EPA] Environmental Research Laboratory, Duluth, MN, USA, and P. Downey, TRAC Laboratories, Inc., Denton, TX, USA, personal communication) and bacterial interferences in whole-effluent acute toxicity tests with fathead minnows have been previously observed in samples of cooling water [6]. An anomaly that confounds interpretation of the C. dubia test in ambient applications has also been documented; C. dubia frequently have higher fecundity in ambient waters than they do in control water (reconstituted or laboratory water) [7].…”
Section: Introductionmentioning
confidence: 69%
“…Large variation in survival of fathead minnow larvae among replicates has been observed by others (T. Norberg-King, U.S. Environment Protection Agency [EPA] Environmental Research Laboratory, Duluth, MN, USA, and P. Downey, TRAC Laboratories, Inc., Denton, TX, USA, personal communication) and bacterial interferences in whole-effluent acute toxicity tests with fathead minnows have been previously observed in samples of cooling water [6]. An anomaly that confounds interpretation of the C. dubia test in ambient applications has also been documented; C. dubia frequently have higher fecundity in ambient waters than they do in control water (reconstituted or laboratory water) [7].…”
Section: Introductionmentioning
confidence: 69%
“…Other investigators also reported anomalous test results using P. promelas that were believed to be due to a naturally occurring biological interference characterized by filamentous growths on the larvae. That study also indicated UV exposure because filtration was effective for controlling the effects of the pathogens [4]. In data compiled by the Wisconsin Department of Natural Department of Natural Resources, Madison, Wisconsin, USA, 26% of chronic P. promelas WET tests (n ϭ 1,496 tests) showed unacceptable survival (Ͻ80%) in receiving water controls as compared with laboratory-water controls (2.9%).…”
Section: Introductionmentioning
confidence: 84%
“…For instance, increased hardness is a feature of some effluents, which can have an adverse effect on daphnids irrespective of contaminant concentrations [6]. Variations in salinity and total dissolved solids concentrations can significantly affect WET test organisms [71–73]. So too can the presence of other biota in the effluent ([72]; Table 1).…”
Section: Level Of Protectionmentioning
confidence: 99%